Enhanced phosphate absorption in intestinal epithelial cell‐specific NHE3 knockout mice. (11th January 2022) - Xue, Jianxiang; Thomas, Linto; Murali, Sathish Kumar; Levi, Moshe; Fenton, Robert A.; Dominguez Rieg, Jessica A.; Rieg, Timo
Abstract: Aims: The kidneys play a major role in maintaining Pi homeostasis. Patients in later stages of CKD develop hyperphosphatemia. One novel treatment option is tenapanor, an intestinal‐specific NHE3 inhibitor. To gain mechanistic insight into the role of intestinal NHE3 in Pi homeostasis, we studied tamoxifen‐inducible intestinal epithelial cell‐specific NHE3 knockout (NHE3 IEC‐KO ) mice. Methods: Mice underwent dietary Pi challenges, and hormones as well as urinary/plasma Pi were determined. Intestinal 33 P uptake studies were conducted in vivo to compare the effects of tenapanor and NHE3 IEC‐KO . Ex vivo Pi transport was measured in everted gut sacs and brush border membrane vesicles. Intestinal and renal protein expression of Pi transporters were determined. Results: On the control diet, NHE3 IEC‐KO mice had similar Pi homeostasis, but a ~25% reduction in FGF23 compared with control mice. Everted gut sacs and brush border membrane vesicles showed enhanced Pi uptake associated with increased Npt2b expression in NHE3 IEC‐KO mice. Acute oral Pi loading resulted in higher plasma Pi in NHE3 IEC‐KO mice. Tenapanor inhibited intestinal 33 P uptake acutely but then led to hyper‐absorption at later time points compared to vehicle. In response to high dietary Pi, plasma Pi and FGF23 increased to higher levels in NHE3 IEC‐KO mice which was associated with greater Npt2b expression. Reduced renal Npt2c and a trend for reduced Npt2a expression were unable to correct for higher plasma Pi . Conclusion: Intestinal NHE3 has a significant contribution to Pi homeostasis. In contrast to effects described for tenapanor on Pi homeostasis, NHE3 IEC‐KO mice show enhanced, rather than reduced, intestinal Pi uptake.